Maturity Model of Management of Physical Constraints - Pérez-Pravia, Milagros Caridad (2023)
The business system lacks a tool to guide the implementation of good practices in the path of evolutionary improvement of the management of physical restrictions. This research aims to design a maturity model for this management. For this, the maturity models are integrated with the management cycle, there is a model composed of three phases: Planning, Design and Execution, allowing the identification of these levels in an organization in terms of the management of physical restrictions, in addition to a group of reports and analysis of the results that serve as a guide in its strategic projection.